Analysis of the Effect of Cul-de-sacs′ Permeability Factors in Low-Rise Residential Areas on Burglary. Issue 3 (1st September 2017) - Kim, Seungil; Kim, Dahee; Jung, Sungwon
Abstract : Only a few studies so far have analyzed specific environmental factors of cul-de-sacs′ influence on safety from crime. To understand crime, streets′ physical characteristics need to be considered along with the collective sociodemographic characteristics of each region. A model was designed that combines the physical characteristics of cul-de-sacs with the demographic characteristics of neighborhoods to examine the effect of such characteristics on the crime rate in cul-de-sacs. The physical characteristics of cul-de-sacs in a target area were categorized and examined based on connectivity, accessibility, and visibility, In addition to sociodemographic characteristics. A hierarchical linear model was then constructed from the collected data related to connectivity, accessibility, visibility, and sociodemographic characteristics at the neighborhood level. Finally, the results of the analyses were combined to determine their relationship with the crime rate. Except for a few variables, the results are significant for connectivity, visibility, and accessibility, which allows for an explanation of the occurrence of burglaries when sociodemographic factors are additionally accounted for.